2014
DOI: 10.1007/978-3-319-07863-2_48
|View full text |Cite
|
Sign up to set email alerts
|

To Relive a Valuable Experience of the World at the Digital Museum

Abstract: This paper describes a new concept of bodily experience that may be used in the future museum exhibit. An ordinary museum exhibits objects to make themselves talk with their authenticity to visitors, however it does not provide an interaction and vivid context in which they existed. A virtual experience system which creates multisensory stimuli potentially presents the realistic state of valuable artificial objects in the original environments. We think the experience of objects in a particular space is anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The technology integrated in the Sensorama allowed a single person to see a stereoscopic film enhanced with seat motion, vibration, stereo sound, wind, and aromas, which were triggered during the film. Recent research works dealing with immersive multimodal systems are reported in [8,9], also involving individual experiences. On the other hand, the rapid technological advancements of the last years have allowed the development of commercial solutions that integrate a variety of multimodal displays in movie theatres, such as in [10][11][12], where these systems are usually referred to as 4D or 5D cinemas or theatres.…”
Section: Introductionmentioning
confidence: 99%
“…The technology integrated in the Sensorama allowed a single person to see a stereoscopic film enhanced with seat motion, vibration, stereo sound, wind, and aromas, which were triggered during the film. Recent research works dealing with immersive multimodal systems are reported in [8,9], also involving individual experiences. On the other hand, the rapid technological advancements of the last years have allowed the development of commercial solutions that integrate a variety of multimodal displays in movie theatres, such as in [10][11][12], where these systems are usually referred to as 4D or 5D cinemas or theatres.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when referring to cinemas in a wider sense, i.e., movie theatres, the film experience is collective rather than individual-as it was the case of the Sensorama. The existing research works dealing with multimodal technologies and environments [4,5] usually involve individual, rather than collective, experiences, and/or refer only to the involved technology.…”
Section: Introductionmentioning
confidence: 99%